The UFO Encyclopedia: The Phenomena from the Beginning (3rd ed., 2 vol.) by Jerome Clark - Alexander, John B. (Journal of Scientific Exploration, 2020)
With more than 1500 pages, this is a massive undertaking by SSE Dinsdale Award winner, Jerry Clark. This two-volume third edition is buttressed by his decades of research in the field of UFOs. For this encyclopedic effort he is supported by several competent researchers with international reputations. Typically, my reviews of written works by SSE members tend to be quite favorable as I recognize the difficulty of getting our research into print. This work definitely left me conflicted in an attempt to be both fair to the authors and to the potential readers. In general, the material that is included does provide considerable depth to the cases selected for presentation. As this is the third edition, much of that material has been previously published. Clark and his colleagues have in-depth knowledge of many of the earlier cases and these are well represented. What I found most troubling were some glaring omissions that are hard to reconcile with an encyclopedia that suggests it is comprehensive in nature, as opposed to a representation of cases as selected by the chief editor. Absent is the more recent incidences and evidence that have dramatically altered the entire field of UFOlogy. Given the rapid pace of advancement of knowledge, especially since December 2017, it would be nearly impossible for any print medium to keep pace. Here I am addressing the remarkable revelations by the U.S. Department of Defense concerning interactions between military aircraft and unknown objects. Internally these were so significant as to cause the U.S. Navy to publicly publish a policy position acknowledging these events were occurring frequently. However, it is more than the events of just the past two years that are omitted or downplayed. As a prime example, Phil Corso is not mentioned. In 1997, U.S. Army Lt. Col. Corso’s book The Day After Roswell became an international phenomenon. It dominated much of the conversation in the field. Whether one agrees with Corso or not is irrelevant. His book sold more than any other UFO publication by a great margin and he had significant impact on the field. Thus, both Corso and his book should deserve serious consideration.